Kişisel verilerin korunması hakkına yönelik suçların türk ceza hukuku kapsamında incelenmesi - Uyan, Murat (Hasan Kalyoncu Üniversitesi, 2022)
Kişisel veri kavramı ile ilgili gerek ulusal gerekse de uluslararası düzenlemelerde farklı tanımlamalar olsa bile, genel tanımı ile kişisel veri; gerçek bir kişiye ait olup, kişiyi tanımlanabilir kılan tüm bilgilerdir. Kapsamı bakımından, kişisel veri terimi, bir kişiyi başka kişilerden ayırt eden her türlü veri olarak adlandırıldığı için çok geniştir. Kişilere ait kimlik bilgileri, kişilerin iş ve sağlık bilgileri, siyasi görüşlerine ilişkin bilgileri, ekonomik bilgileri gibi bilgileri, kişisel veri kapsamındadır. Mevzuatımızda, 6698 sayılı Kişisel Verilerin Korunması Kanunu ve Türk Ceza Kanunu kapsamında kişisel verilere ve kişisel verilerin korunması hakkının ihlaline yönelik hususlar düzenlemiştir. Although there are various definitions in both national and international regulations regarding the concept of personal data, with its common definition, personal data is all the information that belongs to a real person and makes the person identifiable. With regards to its scope, the term personal data is very broad as it is defined as any kind of data that distinguishes one person from others. Information such as identity information of individuals, job and health information of individuals, information about their political opinions and economic information are within the scope of personal data. In our legislation, issues regarding the violation of the right to personal data and the protection of personal data have been regulated within the scope of the Personal Data Protection Law No. 6698 and the Turkish Penal Code. In this study, basic concepts and important issues related to personal data are discussed in the first part. Then in the second part, within the scope of the Turkish Penal Code, the examination of the right to protection of personal data, the main purpose of the study, has been examined with the regulations and judicial decisions both in domestic and international law, and suggestions on controversial points are presented. Bu çalışmada, birinci bölümde, kişisel verilere ilişkin temel kavramlar ve önemli hususlar ele alınmıştır. İkinci bölümde ise çalışmanın temel amacı olan kişisel verilerin korunması hakkının TCK kapsamında incelenmesi hem iç hukukta hem de uluslararası hukukta yer alan düzenlemeler ve yargı kararları ile incelenmiş olup, tartışmalı noktalara ilişkin öneriler sunulmuştur.

Although there are various definitions in both national and international regulations regarding the concept of personal data, with its common definition, personal data is all the information that belongs to a real person and makes the person identifiable. With regards to its scope, the term personal data is very broad as it is defined as any kind of data that distinguishes one person from others. Information such as identity information of individuals, job and health information of individuals, information about their political opinions and economic information are within the scope of personal data. In our legislation, issues regarding the violation of the right to personal data and the protection of personal data have been regulated within the scope of the Personal Data Protection Law No. 6698 and the Turkish Penal Code. In this study, basic concepts and important issues related to personal data are discussed in the first part. Then in the second part, within the scope of the Turkish Penal Code, the examination of the right to protection of personal data, the main purpose of the study, has been examined with the regulations and judicial decisions both in domestic and international law, and suggestions on controversial points are presented.
Crimes against the right to protection of personal dataexamination within the scope of turkish criminal law
Keywords: Hukuk; Law